BODY SHAMING IN THE QUR’AN: A HUMANISTIC PSYCHOLOGY APPROACH TO HUMANISTIC RESILIENCE - ubaidillah; Siti Nurul Kholifah; Siti Marpuah (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2025)
Since the modification of social communication into digital communication, there has been subordinative social aggression through the crime of body shaming which causes psychological and mental impacts to self-harm or suicide. Degrading and racist acts are intimidative social treatments that are not legally justified, especially in religion. The problem of this research focuses on how the conceptual framework of human resilience as an effort to prevent the crime of psychological body shaming in the Qur'an. Toshihiko Isutzu's method of structural maudu>'i interpretation was used to look at the conceptual and comprehensive framework of key terms with the help of Abraham Harold Maslow's humanistic psychological analysis theory. This study aims to explain the structure of the term body shaming in the Qur'an, the characteristics of the value of body shaming crimes in the Qur'an, and how positive psychological contribution as a concept of self-resilience from the crime of body shaming. Replying to the above formulation, the research produced findings, namely first, the structure of the term about the crime of body shaming in the Qur'an includes three key terms, istahza'a, Sakhara, and Talmizu. Second, the characteristics of negative body shaming values in the Qur'an are explained the prohibition image and identity of personal, social, and group (person-centered), prohibition of opening disgrace and denouncing others (safety and security needs). Third, the urgency of personality education and confidence in self-acceptance as well as understanding differences and wisely communicating by prioritizing appreciation for others (at Tasa>muh baina diya>nah wa insa>niyyah).